Primary Politics : Everything You Need to Know about How America Nominates Its Presidential Candidates. - Kamarck, Elaine (Brookings Institution Press, 2018)
"Explores one of the most important questions in American politics--how we narrow the list of presidential candidates every four years. Focuses on how presidential candidates have sought to alter the rules in their favor and how their failures and successes have led to even more change" -- Provided by publisher.